2017
DOI: 10.1177/2333794x16685190
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies in Communication Versus Documentation of Weight-Management Benchmarks

Abstract: To examine gaps in communication versus documentation of weight-management clinical practices, communication was recorded during primary care visits with 6- to 12-year-old overweight/obese Latino children. Communication/documentation content was coded by 3 reviewers using communication transcripts and health-record documentation. Discrepancies in communication/documentation content codes were resolved through consensus. Bivariate/multivariable analyses examined factors associated with discrepancies in benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous research showed that CHC nurses provide more information verbally in encounters with children and their families than what is documented in the record [16]. Differences between what is communicated and what is documented were found to be in both directions, i.e., what is communicated is not documented, and what is documented is not communicated [25]. The Patient Data Act [26] prescribes that CHC nurses have an obligation to document, and what is not documented did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research showed that CHC nurses provide more information verbally in encounters with children and their families than what is documented in the record [16]. Differences between what is communicated and what is documented were found to be in both directions, i.e., what is communicated is not documented, and what is documented is not communicated [25]. The Patient Data Act [26] prescribes that CHC nurses have an obligation to document, and what is not documented did not occur.…”
Section: Discussionmentioning
confidence: 99%